2020
DOI: 10.1111/cpr.12764
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of miR‐29b‐3p influences heart development and cardiomyocyte proliferation by targeting NOTCH2

Abstract: Objectives microRNA‐29 (miR‐29) family have shown different expression patterns in cardiovascular diseases. Our study aims to explore the effect and mechanism of miR‐29 family on cardiac development. Materials and methods A total of 13 patients with congenital heart disease (CHD) and 7 controls were included in our study. Tissues were obtained from the right ventricular outflow tract (RVOT) after surgical resection or autopsy. The next‐generation sequencing was applied to screen the microRNA expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Besides, H19 has been identi ed as a regulator that targets PPARα of cardiac hypertrophy [25,26]. The results showed that XIST, MALAT1 and H19 possibly regulated other miRNAs involved in cardiac hypertrophy, such as miR-15b [27], miR-19b [28] and miR-29b [29] in our research.…”
Section: Discussionsupporting
confidence: 55%
“…Besides, H19 has been identi ed as a regulator that targets PPARα of cardiac hypertrophy [25,26]. The results showed that XIST, MALAT1 and H19 possibly regulated other miRNAs involved in cardiac hypertrophy, such as miR-15b [27], miR-19b [28] and miR-29b [29] in our research.…”
Section: Discussionsupporting
confidence: 55%
“…Besides, H19 has been identi ed as a regulator that targets PPARα of cardiac hypertrophy (Liu et al, 2016;Zhou et al, 2019). The results showed that XIST, MALAT1 and H19 possibly regulated other miRNAs involved in cardiac hypertrophy, such as miR-15b (Ooi et al, 2014), miR-19b (Li et al, 2019) and miR-29b (Yang et al, 2020) in our research.…”
Section: Discussionsupporting
confidence: 55%
“…Increasing evidence suggests that abnormal expression miR-29a-3p is in association with various heart diseases. For example, its expression is upregulated in the right ventricular outflow tract of congenital heart disease patients [ 16 ]. Moreover, it suppresses cardiomyocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%